The gun [compact disc, unabridged] - Chivers, C. J. (Christopher John) (Tantor Media, 2010)
C. J. Chivers traces the invention of the assault rifle, following the miniaturization of rapid-fire arms from the American Civil War, through World War I and Vietnam, to present-day Afghanistan, where Kalashnikovs and their knockoffs number as many as 100 million, one for every seventy persons on earth. It is the weapon of state repression, as well as revolution, civil war, genocide, drug wars, and religious wars; and it is the arms of terrorists, guerrillas, boy soldiers, and thugs.